Respiratory viral diseases: access to RNA interference therapy - Bitko, Vira (Elsevier Ltd., 2007)
This review summarizes recent experimental achievements in the area of the development of new RNA interference (RNAi) therapeutics for the treatment of viral respiratory diseases. Delivery of short interfering RNA (siRNA) to their intended target tissue remains the biggest problem for most therapeutic applications of these compounds. Appropriate formulations and chemical modifications for improved stability will boost the probability of utilization of RNAi drugs in the clinical applications.